(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article discusses experimental studies of applying ceramic coatings by various methods and means to components of working bodies of agricultural machinery, engines of automobile and tractor machinery. In addition, several ceramic coating materials and their application processes were carefully considered, the use of ceramic coating optimization methods, as well as dispersion analysis were investigated.